The Realization of Presuppositions in Harry Potter Philosopher’s Stone - nastiti ardita sari; Januarius Mujiyanto; Zulfa Sakhiya (Universitas Negeri Semarang, 2023)
This study aimeld at investigating the realization of presupposition in Harry Potter philosopher’s stone and the implication of presupposition on the teaching of English as a foreign language in Indonesia. Thel design of this study focused on pragmatic analysis, and this study employed a qualitative approach. This relselarch useld script and movie of Harry Potter philosophers stone as thel sourcel of thel data. The researcher used an instrument based on the theory proposed by Yule’s (1996). The categories are existential presupposition, structural presupposition, counter factual presupposition, factive presupposition, non-factive presupposition, and lexical presupposition. The finding of this research shows that five among the six types of presupposition were found in the movie. The whole data of the types of presupposition are 58 data, 19 are Existential Presupposition, 14 are Structural Presupposition, 13 are Factive Presupposition, 11 are Counter Factual Presupposition, 1 is Non-Factive Presupposition, and the last 0 Lexical Presupposition found in Harry Potter philosopher’s stone movie. And all the types of presupposition implied on teaching English as a foreign language through various manners. Presupposition is the important thing, thus the writer suggests the readers of this research, the listeners of a speech, the politician and the next researcher that understanding the presupposition and its types will reduce the misunderstanding in a communication and give more information than just stated.